Kepatuhan Penggunaan Masker dalam Upaya Pencegahan Penularan Covid-19 di Kota Samarinda - Apriyani Apriyani; Rindha Mareta Kusumawati; Kartina Wulandari (HB PRESS, 2022)
Cases in Indonesia are still showing an increase in the number of positive cases exposed to COVID-19, so the government has implemented various efforts to reduce the number of positive cases in Indonesia. One of them is the policy of using masks. The use of mask is part of a comprehensive series of prevention and control measures that can limit the spread of certain viral respiratory tract diseases, including COVID-19. Masks can be used to protect healthy people (used to protect themselves when in contact with infected people) or to control the source (used by an infected person to prevent further transmission). One of the methods to increase compliance with wearing masks is to increase patient understanding of the importance of preventing transmission of the corona virus by obediently wearing masks. The results showed that respondents with low knowledge in the use of mask were 51.7% with a total of 120 respondents and those with good knowledge were 48.3% with a total of 112 respondents. Respondents with poor compliance in using masks were 39.7% with a total of 92 respondents and those with good compliance in using masks were 60.3% with a total of 140 respondents. The results of the chi-square test showed that there was no relationship between public knowledge and compliance with the use of mask in Samarinda City with a p-value of 0.146 (p-value>0.05).